A survey on the causes of waterproofing defects in government office buildings, Putrajaya / Nurulhuda Abd Hadi - Abd Hadi, Nurulhuda (2012)
Waterproofing system is required to prevent the water from penetrate to the surface. Waterproofing system acts as the supporter to protect the building structure and building finishes from failure or deterioration. This dissertation is prepared in order to achieve some specific aim and objective of the causes waterproofing defect in building through the three objectives which is to identify the types of waterproofing defect in the office building, to investigate the causes of waterproofing defects in government's office building and to recommend best practice to ensure good waterproofing system installation in the building. It is important to know the types of waterproofing system implement in the building, especially at the crucial area such as roof, basement, toilet and jointing. The basic theory of waterproofing system such as definition and the principle of waterproofing is explained in the literature review. Besides that, research methodology that have been applied in the three selected case study to collect data based on the literature review, observation, sample of questionnaire and interview with the people that involve with the maintenance field. The data analysis and finding is done. From the result, the conclusion and recommendation is made. It indicates the proper selection of waterproofing during the design stage is very important in order to prevent the causes of waterproofing defect in the building.